Growth of carbon nanotubes inside boron nitride nanotubes by coalescence of fullerenes: towards the world’s smallest co-axial cable - Walker, Kate E.; Rance, Graham A.; Pekker, Áron; Tóháti, Hajnalka M.; Fay, Michael W.; Lodge, Rhys W.; Stoppiello, Craig T.; Kamarás, Katalin; Khlobystov, Andrei N. (Wiley, 2017)
The use of boron nitride nanotubes as effective nanoscale containers for the confinement and thermal transformations of molecules of C60-fullerene has been demonstrated. The gas-phase insertion of fullerenes into the internal channel of boron nitride nanotubes yields quasi-one-dimensional arrays, with packing arrangements of the guest-fullerenes different to those in the bulk crystal and critically dependent on the internal diameter of the host-nanotube. Interestingly, the confined fullerene molecules (i) exhibit dynamic behaviour and temperature-dependant phase transitions analogous to that observed in the bulk crystal and (ii) can be effectively removed from within the internal channel of nanotubes by excessive sonication in organic solvent, indicating weak host-guest interactions. The thermal treatment of fullerenes confined within nanotubes at 1200 °C in argon triggers the polymerisation and coalescence of the guest-fullerenes into carbon nanotubes inside boron nitride nanotubes affording a hybrid nanostructure – the world’s smallest coaxial cable – on a preparative scale, as confirmed by high resolution bright field transmission electron microscopy (TEM) imaging and electron energy loss spectroscopy, energy filtered transmission electron microscopy (EELS, EFTEM) elemental mapping and UV-vis absorption spectroscopy.